Environmental concern as a green stimulus: An S-O-R approach to sustainable fashion purchase intention in Indonesia - Fatullah Razi (Priviet Social Sciences Journal, 2026)
Despite the increasing global awareness, sustainable fashion consumption remains inconsistent. This study applies the stimulus-organism-response (S-O-R) model to examine the process through which environmental concern acts as a green stimulus influencing consumers’ internal psychological activation and purchase intention. Using data from Indonesian consumers analyzed through structural equation Modeling based on Partial Least Squares (PLS-SEM), incorporating 5,000 bootstrap resamples, the findings indicate that environmental concern has a statistically significant positive effect on purchase intention (β = 0.738; t = 18.756; p < 0.001; R² = 0.545; f² = 1.196; SRMR = 0.067). All reliability and validity criteria were met (α > 0.80, CR > 0.85, and AVE > 0.56). The findings confirm that environmental concerns function as psychological and emotional stimuli that shape sustainable purchase behavior. This study broadens the application of the S-O-R framework in sustainability research and offers practical guidance for eco-fashion marketers to design emotionally engaging green messages targeting emerging market consumers.